The Effect of Interaction and Website Environment Qualities Towards E-Loyalty: A Case Study of Online Hotel Booking in Indonesia and Thailand - Rizal , Fikri Samsu; Munandar , Jono M.; Sarma, Ma’mun (Institut Pertanian Bogor, 2021)
Online hotel booking is a method of renting a place through the internet. Today, people are becoming users of online rental properties as a necessity and lifestyle. Indonesia and Thailand as tourist destinations indicates a large population that have potential for the online property rental business. This study will analyze the effect of interaction quality, website environment quality that have an impact on customer loyalty toward this product. In this study, data was collected by a questionnaire that has been given, the authors used Structural Equation Modeling - Partial Least Square (SmartPLS) for analysis method. This method is used to determine the number of online hotel booking users so that it will be seen how the effect of interaction quality and website environment quality has an impact on e-Loyalty. In both countries, the quality of interaction has a positive and significant effect on e-loyalty. The coefficient value of the interaction quality parameter in the Indonesian model has a value of 0.544. The results of the significance test showed that the website environment quality variable had a positive and significant effect in both countries with T-statistical test results > 1.96 and P-values less than 0.05. This study examines the direct relationship between the interaction quality and website environment quality variables on e-Loyalty. This research can be additional knowledge related to the determinants of loyalty found in online businesses. In addition, the research also provides a new picture of the online lodging service business in two countries, namely Indonesia and Thailand